Mosquitoes (Diptera, Culicidae) inhabiting foliar tanks of Guzmania brasiliensis Ule (Bromeliaceae) in central Amazonia, Brazil - Torreias,Sharlene Roberta da Silva (2010)
Mosquitoes in the family Culicidae develop their immature forms in different environments depending on various circumstances. This study represents the first contribution to the ecological knowledge of culicids living in the bromeliad G. brasiliensis. The objectives of the study were to compare the Culicidae fauna of bromeliads in two seasonal periods, analyzing their abundance, richness and the influence of pH, conductivity and water volume, on the populations. Sampling was done at Reserva Adolpho Ducke, Manaus, Amazonas, Brazil between 2003 and 2005. Six samplings were done in the rainy season and six in the dry season. On each sampling day, six terrestrial and six epiphytic bromeliads, totaling 144 sampling units, were retrieved. A total of 444 immature mosquitoes were collected, distributed in the following species: Culex (Microculex) stonei Lane & Whitman, Culex (Microculex) chryselatus Dyar & Knab, Culex (Microculex) sp., Wyeomyia (Hystatomyia) autocratica Dyar & Knab and Wyeomyia (Hystatomyia) splendida Bonne-Wepster & Bonne. The relationship between abundance of Culicidae and sampling period was not significant, although abundance was higher in the dry period. There were significant correlations between water volume and the abundance (p = 0.003) and richness (p = 0.001) of culicids. The pH was positively related to the occurrence of the species Wy. autocratica (p= 0.010) and Wy. splendida (p= 0.006), demonstrating the influence of this factor in the structuring of bromeliad-inhabiting communities.